2015
DOI: 10.1007/s00894-015-2696-z
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the unfolding pathway and identification of thermally sensitive regions of phytase from Aspergillus niger by molecular dynamics simulations

Abstract: Thermal stability is of great importance in the application of commercial phytases. Phytase A (PhyA) is a monomeric protein comprising twelve α-helices and ten β-sheets. Comparative molecular dynamics (MD) simulations (at 310, 350, 400, and 500 K) revealed that the thermal stability of PhyA from Aspergillus niger (A. niger) is associated with its conformational rigidity. The most thermally sensitive regions were identified as loops 8 (residues 83-106), 10 (161-174), 14 (224-230), 17 (306-331), and 24 (442-444)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
4
1
Order By: Relevance
“…The number of hydrogen, ionic and disulfide bond interactions is believed to have a strong correlation with thermostability (Zhang 2007;Liao, et al, 2013;Fei et al, 2013;Hesampour et al, 2015;Kumar et al, 2015;Tan et al, 2016;Han et al, 2018;Li et al, 2019;Zhang et al, 2020). However, here we show that, for these enzymes, this is not true.…”
Section: Quantification and Analysis Of Interactions Of The Structura...contrasting
confidence: 50%
See 1 more Smart Citation
“…The number of hydrogen, ionic and disulfide bond interactions is believed to have a strong correlation with thermostability (Zhang 2007;Liao, et al, 2013;Fei et al, 2013;Hesampour et al, 2015;Kumar et al, 2015;Tan et al, 2016;Han et al, 2018;Li et al, 2019;Zhang et al, 2020). However, here we show that, for these enzymes, this is not true.…”
Section: Quantification and Analysis Of Interactions Of The Structura...contrasting
confidence: 50%
“…The association between the structure and the biochemical properties of enzymes can provide relevant information about factors that affect stability and catalytic activity. Several methods have been used for this purpose, including comparative sequence, structure analysis, molecular dynamics studies, or even the evaluation of random or rational mutations on enzyme activity (Zhang 2007;Liao, et al, 2013;Fei et al, 2013;Hesampour et al, 2015;Kumar et al, 2015;Tan et al, 2016;Han et al, 2018;Li et al, 2019;Zhang et al, 2020;Acquistapace et al, 2022). In this study, we report a comparative approach between sequences, threedimensional structures and biochemical characteristics of phytases already characterized and described in the literature, adopting factors such as: hydrogen, ionic and Van der Waals (VdW) interactions and disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Some regions of PHYA from A. niger (the salt bridges between Glu125-Arg163, Asp299-Arg136, Asp266-Arg219, Asp339-Lys278, Asp335-Arg136, and Asp424-Arg428) were predicted as thermolabile by bioinformatic tools given their expansion upon the increase of temperature. This data could be the basis to engineer novel thermostable phytases with desirable properties [102].…”
Section: Thermostability: An Issue For Industrial Applicationmentioning
confidence: 96%
“…By increasing the temperature, most thermally sensitive regions, including loops 8, 10, 14, 17 and 24, showed intense increments in RMSF values. It was concluded that the location of the salt bridge was more important compared to the number of salt bridges for thermostability [22].…”
Section: Aspergillus Phytasesmentioning
confidence: 99%